Pengembangan Material Sorben Berbasis Zeolite dan Clay Alam se-bagai Media Desalinasi Air Laut - Wibowo, Edy; Rokhmat, Mamat; Sutisna, Sutisna; Khairurrijal, Khairurrijal; Abdullah, Mikrajuddin (Jurnal Matematika dan Sains, 2017)
We have developed a sorbent based natural materials for seawater desalination application. We used clays, soil, rock and zeolite as raw materials. We conducted a thermal activation process to improve the sorption ability of the materials. The sorption ability of materials were tested to reduce the salinity of seawater and it is expressed by the reduction efficiency. The highest reduction efficiency (4%) was obtained from the activation of the soil at temperature of 600 ° C and the zeolite at a temperature of 200 ° C. It can be seen that the reduction efficiency was linearly increased with the increase of the doses of sorbent. We observed that the sorption ability of zeolite can be enhanced through thermal activation at a relatively low temperature so that it was potentially used as a low-cost sorbent material for seawater desalination.